A comparative in-silico analysis of autophagy proteins in ciliates - Aslan,Erhan; Küçükoğlu,Nurçin; Arslanyolu,Muhittin (PeerJ, 2017)
Autophagy serves as a turnover mechanism for the recycling of redundant and/or damaged macromolecules present in eukaryotic cells to re-use them under starvation conditions via a double-membrane structure known as autophagosome. A set of eukaryotic genes called autophagy-related genes (ATGs) orchestrate this highly elaborative process. The existence of these genes and the role they play in different eukaryotes are well-characterized. However, little is known of their role in some eukaryotes such as ciliates. Here, we report the computational analyses of ATG genes in five ciliate genomes to understand their diversity. Our results show that Oxytricha trifallax is the sole ciliate which has a conserved Atg12 conjugation system (Atg5-Atg12-Atg16). Interestingly, Oxytricha Atg16 protein includes WD repeats in addition to its N-terminal Atg16 domain as is the case in multicellular organisms. Additionally, phylogenetic analyses revealed that E2-like conjugating protein Atg10 is only present in Tetrahymena thermophila. We fail to find critical autophagy components Atg5, Atg7 and Atg8 in the parasitic ciliate Ichthyophthirius multifiliis. Contrary to previous reports, we also find that ciliate genomes do not encode typical Atg1 since all the candidate sequences lack an Atg1-specific C-terminal domain which is essential for Atg1 complex formation. Consistent with the absence of Atg1, ciliates also lack other members of the Atg1 complex. However, the presence of Atg6 in all ciliates examined here may rise the possibility that autophagosome formation could be operated through Atg6 in ciliates, since Atg6 has been shown as an alternative autophagy inducer. In conclusion, our results highlight that Atg proteins are partially conserved in ciliates. This may provide a better understanding for the autophagic destruction of the parental macronucleus, a developmental process also known as programmed nuclear death in ciliates.
Keywords: Autophagy proteins; Ciliates; Nucleophagy; Phylogeny; In silico; Sequence annotation; Conjugation; Programmed nuclear death